THE ROLE OF THE MODALITY CATEGORY IN THE WORLD OF MEDIA - Yodgorova Zebo (Galaxy International Interdisciplinary Research Journal, 2022)
Mass media (media), first of all, influence the knowledge of the audience, form their media-view of the world. Dividing the image of the world into components has the same conditional appearance as the separation of personal and social reality. Firstly, if social reality is considered as an integral attribute of human collective nature, secondly, personality cannot be formed outside of society. In this regard, I.V. Rogozina expresses the following opinion: "... personal and social reality is a phenomenon related to each other, social and personal reality is embodied in a person's image of the world, and mass media is one of the main integrating factors in the modern world [8].